Analysis of the Effect of Provincial Minimum Wage and Inflation on Household Expenditure Levels in Java Island - Francisca Catur Arini; Josephine Wuri; Yuliana Rini Hardanti; Antonius Budisusila (Riviera Publishing, 2026)
The economic condition of Java Island, as the centre of national industrial and trade activities, is strongly influenced by the dynamics of wages and the prices of goods and services. Changes in the Provincial Minimum Wage (PMW) and inflation rate are two key factors that can affect purchasing power and household spending patterns. Based on this, this study aims to analyse the effects of PMW and inflation on household expenditure levels in Java Island over the period 2018–2024. This research employs a panel data regression analysis using the random effects model. The results show that PMW has a positive and significant effect on household expenditure, indicating that an increase in the minimum wage can enhance purchasing power and drive consumer spending. Conversely, inflation has a minimal impact on household expenditure. Simultaneously, both PMW and inflation significantly influence household expenditure, underscoring the importance of synergy between wage policy and price control in maintaining economic stability and public welfare.